2011
DOI: 10.1002/pca.1289
|View full text |Cite
|
Sign up to set email alerts
|

Validated high‐performance thin‐layer chromatographic method for the quantification of thymoquinone in Nigella Sativa extracts and formulations

Abstract: The HPTLC method developed was found to be relatively simple, rapid and accurate for the routine analysis of TQ in extracts, marketed oils, polyherbal and in-house formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 13 publications
0
23
2
1
Order By: Relevance
“…However in 2014, Salmani et al reported that the UV-vis spectra of thymoquinone can be characterized by a prominent peak around 254-257 nm. Thymoquinone, thymol, thymohydroquinone, dithymoquinone and many others are among the active compounds isolated from the seed of N. sativa which responsible in providing the therapeutic properties (Zribi et al, 2014). Hydroquinone is described to give another peak around 290 nm but no distinguished peak is observed at 294 nm, although the same wavelength was used in other study to detect thymoquinone (Salmani et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However in 2014, Salmani et al reported that the UV-vis spectra of thymoquinone can be characterized by a prominent peak around 254-257 nm. Thymoquinone, thymol, thymohydroquinone, dithymoquinone and many others are among the active compounds isolated from the seed of N. sativa which responsible in providing the therapeutic properties (Zribi et al, 2014). Hydroquinone is described to give another peak around 290 nm but no distinguished peak is observed at 294 nm, although the same wavelength was used in other study to detect thymoquinone (Salmani et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…HPLC and GC-MS in quantifying the N. sativa seeds extract (Velho et al, 2011;Avula et al, 2010;Lupidi et al, 2010). However, these two common quantifying methods are relatively expensive and time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…It produces capsule-like fruit full of numerous white trigonal seeds which turn black upon exposure to air after the fruit capsule matures and opens [41]. The black seeds also called black cumin, or black caraway seed are the richest source of its bioactive compounds including thymoquinone (TQ; 2-isopropyl- 5-methyl-1, 4-benzoquinone) [31, 36, 42]. Thymoquinone (TQ) is the most abundant bioactive component in the volatile oil from Nigella sativa black seeds [43, 44]; ranging from 18.4–24.0% [4447] to as high as 27.8 – 57% TQ [31, 36, 37, 42, 48, 49] depending on where the plant is cultivated and how the oil is extracted [39, 50].…”
Section: Introductionmentioning
confidence: 99%
“…The oil and TQ have also shown potent anti-inflammatory effects on several inflammation-based models including experimental encephalomyelitis, colitis, peritonitis, asthma, and arthritis through suppression of pro-inflammatory mediators [31, 37, 46, 50, 54, 58, 59]. Additionally, studies show that TQ possess neuroprotective [46, 47, 6062], antimicrobial [42, 50], antidiabetic [42, 50, 63], anticancer [34] and beneficial immunomodulatory properties [36, 44, 54]. …”
Section: Introductionmentioning
confidence: 99%
“…The presence of volatile components was confirmed by GC/MS spectroscopy whereas UV/Vis spectral analysis was performed for presence of TQ. The total phenolic content in MNS was quantified by Folin-Ciocalteu procedure[18], the percentage saponins (mg/100 mg) was estimated by anisealdehyde-sulphuric acid method[19] while the quantification of TQ was done by reported HPTLC method[20]. The IC 50 values obtained for MNS extracts for inhibition of free radicals was determined by free radical (2,2-diphenyl-1-picrylhydrazyl (DPPH)) scavenging activity[21] whereas the IC 50 value for inhibition of superoxide radical was performed by standard reported methods[22].…”
Section: Methodsmentioning
confidence: 99%